Omelchenko L. F. The comic connotation in architectonics of English telescopic nomination - Omelchenko L. F. (Philological Treatises, 2020)
The article focuses its attention on such notion as “phemomenon of comism” and and its manifestation in telescopic nomination. The conducted research reveals that comic composites are widely used in modern American, British and Ukrainian journalism. The mechanism of comic telescopism creation has a nature of game and is realized under the condition of background pejorativeness and more seldom of background ameliorativeness.